Cultural evolution in the wild: tracking the landscape of learning in bird song - Merino Recalde, N (2023)
The songs of some birds are learnt, much like human music and languages, and they change over time—they evolve culturally. Learning is imperfect and more likely to occur from nearby individuals, and this simple fact opens the door for behaviours to evolve differently in distinct populations. When these differences accumulate and persist over time, cultural traditions emerge. The resulting cultures can be transient or long-lasting, disorderly diverse, or monolithically uniform. This thesis addresses some of the challenges associated with studying cultural diversity in natural populations and provides empirical evidence of factors that drive change and stability within vocal cultures.